Co‐Polymer Carrier with Dual Advantages of Cartilage‐Penetrating and Targeting Improves Delivery and Efficacy of MicroRNA Treatment of Osteoarthritis. Issue 6 (25th December 2022) - Zhao, Yipu; Deng, Xudong; Tan, Shenxing; Zhang, Jie; Han, Jiangfan; Wang, Xue; Pei, Jiawei; Li, Hui; Deng, Xiaoni; Yin, Chong; Yin, Dachuan; Tian, Ye; et al.
Abstract: Osteoarthritis (OA) is a debilitating joint disease affecting nearly 400 million people with no efficient etiological therapies. OA is primarily identified by cartilage destruction, and gradual degeneration of the whole joint would happen when the OA progresses. Hence, cartilage has been identified as the primary therapeutic target of OA. Unfortunately, numerous barriers block the delivery of therapeutic agents into cartilage, including avascular traits and high hardness of the extracellular matrix. Herein, a cartilage‐targeting peptide (CAP) modified polyvinylamine (PVAm)‐ poly (lactic‐co‐glycolic acid) (PLGA) copolymer (CAP‐PVAm‐PLGA) is designed, which can form spherical nanoparticles with the r‐miR‐140 (CPP‐NPs). CPP‐NPs possessed enhanced mechanical properties due to the introduction of PLGA to vehicles. Meanwhile, CAP endowed the cartilage targeting which facilitated CPP‐NPs localization in cartilage. With such dual advantages, CPP‐NPs exhibited outstanding penetrability and accumulation in cartilage even subchondral bone, and can penetrate to a depth of 1000 µm into human cartilage. The degeneration area of cartilage is reduced by 65% and synovial inflammation score by 80% in OA mice, and the microarchitecture of subchondral bone is also ameliorated. These studies established a promising platform for therapeutic RNA delivery in OA therapy that overcame the cartilage barriers. Abstract : Co‐polymer nanoparticles (CPP‐NPs) are designed for improving RNA delivery for OA therapy with high penetrability and cartilage targeting advantages. PLGA modification brought higher penetration by enhancing mechanical properties, and CAP decoration further endowed the nanoparticle with cartilage targeting. CPP‐NPs overcome the biological barriers for anti‐arthrosis RNA delivery and thus hold superior OA therapy effects.